Systematic review of teaching behavioral assessment methods in Applied Behavior Analysis (Brazilian Journal of Behavioral and Cognitive Therapy, 2025)
Assessment is essential in interventions based on Applied Behavior Analysis (ABA). This review sought to systematize studies that taught the implementation of behavior assessment methods or instruments, based on PRISMA. The searches were conducted in the PsycINFO, PubMed, ERIC, Periodicos Capes and Web of Science databases, with the terms “behavior assessment” OR “behavioral assessment” OR “development assessment” AND “caregiver training” AND “staff training” AND “teacher training” AND “parent training”, in English. Among the 717 documents identified, 39 of them met the eligibility criteria. Results demonstrated that teachers were the most frequent participants, that the components of Behavioral Skills Training (BST) were the most used teaching procedures and that most studies taught how to conduct experimental functional analysis. The relevance of teaching teachers to identify the function of interfering behaviors and the scarcity of studies that taught the implementation of instruments to verify skills and behavioral deficits are discussed.
Keywords: applied behavior analysis; behavior assessment; training; autism spectrum disorder